(untitled) (Annals of Medical Research, 2023)
Aim: In idiopathic scoliosis (IS), the mechanism of action of the pain that occurs, especially in the back and neck region, with the increase in curvature, is not known exactly. In the study, the relationship between these pains and the mediastinum was investigated. Materials and Methods: The study, which was planned retrospectively, included 25 individuals with IS (Lenke Type I) and 21 healthy individuals. Individuals with IS determined the regions where they felt the most pain on the body diagram. The lung and mediastinal volumes of the participants were measured in mm3 on computed tomography (CT) images. The ratios of the area occupied by the lung and mediastinum in the thoracic cavity were calculated in each group. The obtained data were evaluated using the IBM SPSS 23.0 program, and p<0.05 was considered statistically significant. Results: There was no significant difference between the two groups in terms of baseline characteristics (p˃0.05). It was determined that individuals with IS felt the most pain in the 3rd, 4th, and 5th cervical and 2nd, 3rd, 4th, 5th, and 6th thoracic spinal nerve dermotomas regions. Compared to the control group, the area covered by the lung in the thoracic cavity decreased by 50% in the IS group, while the area covered by the mediastinum increased at the same rate (p<0.001). Conclusion: We think that the pain that occurs in the neck and shoulder region with the increase in the degree of curvature in individuals with IS with a major curvature in the thoracic region (Lenke Type I) is referred to as pain originating from the mediastinum.